P081 The immunological role of intestinal adipose tissue in dextran sodium sulfate-induced colitis. (16th January 2018) - Letizia, M; Schmidt, F; Glauben, R; Weidinger, C; Siegmund, B
Abstract: Background: Inflammatory bowel disease (IBD) is caused by complex interactions of dysregulated immune responses, defects in the intestinal epithelial barrier and translocating microbiota. IBD includes Crohn's disease (CD) and ulcerative colitis. CD is characterised by the presence of creeping fat. Although the presence of creeping fat positively correlates with transmural inflammation, its functional nature is largely unknown. The most used experimental model for IBD employs dextran sodium sulfate (DSS) to induce epithelial damage and thus colon inflammation. Although the immune cell composition of colon lamina propria in DSS-induced colitis has already been investigated, little is known about the mesenteric fat compartment. Therefore, in order to assess the immunological involvement of mesenteric fat in DSS-induced colitis we aimed to characterise the mesenteric fat immune cell compartment in comparison to the lamina propria compartment. Methods: C57BL/6 mice were fed 2.5% DSS in their drinking water for 5 days to induce acute colitis. In order to induce chronic inflammation mice were fed 2.0% DSS in their drinking water for 7 days followed by 7 days of water for five cycles. Immune cells were isolated from mesenteric fat, gonadal fat, mesenteric lymph nodes and lamina propria and stained with phenotypic and functional markers for T cells and myeloid cells. Cells were analysed by a flow cytometer. Results: No significant differences among myeloid or lymphoid cells were detected when comparing mesenteric and gonadal fat in acute colitis. However, we observed specific changes in the mesenteric fat, but not in gonadal fat of mice with chronic inflammation. CD11b + Ly6C + monocytes decreased in frequency and number while CD11b + F4/80 + CD11c + pro-inflammatory macrophages showed lower expression of MHC II in mesenteric fat after five cycles of DSS treatment. Cytobank analysis allowed us to detect a rare population of cells CD11b hi Ly6C int F4/80 low that expressed high level of IL-6 in both fat depots of control mice. Interestingly, the frequency of CD11b hi Ly6C int F4/80 low cells significantly decreased only in mesenteric fat of mice with chronic inflammation. Conclusions: Our data suggest a specific involvement of the mesenteric fat in chronic but not in acute DSS-induced intestinal inflammation. Particularly, they indicate a possible stop of monocyte infiltration followed by a switch of macrophage phenotype in the mesenteric fat after a chronic exposure to DSS. Further analyses are needed in order to assess whether the DSS-induced colitis model is able to mimic the role of creeping fat in CD adequately.